Successful Treatment of Recurrent Pulmonary Mucormycosis in a Renal Transplant Patient: A Case Report and Literature Review. (13th March 2017) - Martin, Morgan S.; Smith, Alison A.; Lobo, Monica; Paramesh, Anil S.
Abstract : Background. We describe the unusual case of a recently transplanted cadaveric renal transplant recipient who presented with recurrent pulmonary mucormycosis. Case Report. An 18-year-old man with end stage renal disease secondary to congenital renal agenesis status after cadaveric kidney transplant 4 months before presented with acute onset of fever, hemoptysis, and back pain. The patient underwent an emergent left lower lobectomy due to the critical nature of his illness. He was also treated with amphotericin with resolution of his symptoms. One week later, he had evidence of recurrent disease on imaging with a surgical site infection. He underwent reexploration with evacuation of an empyema and debridement of a surgical site infection. He was continued on IV antifungal therapy with isavuconazonium and amphotericin. Radiographic clearance of disease with three months of treatment was apparent with no evidence of recurrence at seven-month follow-up. Discussion. Opportunistic infections in solid organ transplant patients represent a significant source of morbidity and mortality. Most patients are treated with prophylactic anti-infective agents. However, rare infections such as pulmonary mucormycosis remain a risk. The transplant physician must be aware of these uncommon infections and their treatment strategies, including the management of uncommon recurrent disease.